2021
DOI: 10.3390/ijms222111973
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Applications to Reveal Molecular Mechanisms of Gene Expression Regulation in Model Organisms

Abstract: Gene expression regulation at the transcriptome, genome, cell, and tissue levels is a complex phenomenon demanding the development of bioinformatics tools [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Decreased GFR is strongly associated with the prevalence and mortality of COVID-19, and chronic metabolic diseases resulting in CKD, such as diabetes, hypertension, and obesity, are also related to COVID-19 mortality (9). In this study, we collected three datasets and used a computational network data analysis method to discover gene expression patterns and molecular pathways of AKI, CKD, and COVID-19 and identify molecular targets of potential biomarkers, providing more treatment options for different disease conditions (51)(52)(53). By analyzing transcriptional profiles of SARS-CoV-2, AKI, and CKD to identify genes with altered expression in SARS-CoV-2 infection implicated in the pathogenesis of AKI and CKD, we report novel interaction mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased GFR is strongly associated with the prevalence and mortality of COVID-19, and chronic metabolic diseases resulting in CKD, such as diabetes, hypertension, and obesity, are also related to COVID-19 mortality (9). In this study, we collected three datasets and used a computational network data analysis method to discover gene expression patterns and molecular pathways of AKI, CKD, and COVID-19 and identify molecular targets of potential biomarkers, providing more treatment options for different disease conditions (51)(52)(53). By analyzing transcriptional profiles of SARS-CoV-2, AKI, and CKD to identify genes with altered expression in SARS-CoV-2 infection implicated in the pathogenesis of AKI and CKD, we report novel interaction mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…BPs we found to be associated with integrinmediated signaling pathways. Previous studies (26)(27)(28) have shown that integrin alpha V (AV) stimulates the proliferation and activation of renal fibroblasts through TGF signaling, thereby promoting fibrosis (29). The loss of integrin AV has been shown to protect against renal fibrosis in a unilateral ureteral obstruction (UUO), and thus, integrin AV intervention is a key factor in the treatment of CKD characterized by renal fibrosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…A correct understanding of the mechanism of the occurrence and development of hepatocellular carcinoma is crucial to correctly understand the disease and find effective treatment amplification [ 20 22 ]. Bioinformatics is an emerging discipline that can be applied to reveal the molecular mechanisms of gene expression regulation in model organisms [ 23 ]. In our study, we first downloaded the GSE101432 dataset from Gene Expression Omnibus (GEO) data and obtained a series of upregulated and downregulated genes through bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%